Perbandingan Efektivitas Pembelajaran Menggunakan Metode Ceramah dan Media Gambar pada Materi Dinasti Umayyah di Madrasah Tsanawiyah Negeri Kota Palopo - Azhar Habibullah; Marwiyah; Muhammad Yamin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the comparative effectiveness of the lecture method and image media in teaching the Umayyad Dynasty material at Madrasah Tsanawiyah Negeri Palopo City. This study applied a quasi-experimental design with a quantitative approach using a pretest-posttest control group design to compare the effectiveness of the lecture method and image media on students’ learning outcomes in the Umayyad Dynasty material. The sample consisted of two classes, namely the experimental class using image media and the control class using the lecture method. The study employed a saturated sampling technique, in which the entire population was used as the research sample. Data collection techniques included tests, questionnaires, observations, and interviews. Data analysis was conducted using descriptive and inferential statistics through the t-test. The results showed that image media were more effective than the lecture method, as indicated by the increase in the average score of the experimental class from 58 to 81 (an increase of 23 points), while the control class only increased from 57.33 to 59.33 (an increase of 2 points). Student activity in the experimental class reached 100% (very good), whereas the control class only reached 40% (poor). Student responses were also higher in the experimental class (85%) compared to the control class (75%). The limitations of this study lie in the limited sample size and the research scope, which only focused on one learning material. Therefore, future studies are recommended to involve broader samples and combine various instructional media in order to obtain more comprehensive results